2013
DOI: 10.1071/fp12270
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial patterns of soil water extraction and drought resistance among genotypes of a perennial C4 grass

Abstract: The objective of this study was to investigate patterns of soil water extraction and drought resistance among genotypes of bermudagrass (Cynodon spp.) a perennial C 4 grass. Four wild Australian ecotypes (1-1, 25a1, 40-1, and 81-1) and four cultivars (CT2, Grand Prix, Legend, and Wintergreen) were examined in field experiments with rainfall excluded to monitor soil water extraction at 30-190 cm depths. In the study we defined drought resistance as the ability to maintain green canopy cover under drought. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Surface soil drying is very common during progressive drought and can have a profound impact on root growth, viability and functionality in turfgrass (Huang, 1999). In another study involving bermudagrass, Zhou, Lambrides, Roche, Duff, and Fukai (2013) reported that drought resistant genotypes extracted more soil water than drought sensitive ones, especially at depths from 50-110 cm, resulting in lower canopy temperature, higher photosynthetic rates and relative water contents in leaves. Fuentealba et al (2015) also reported more uniform root distribution throughout the soil profile in common bermudagrass.…”
Section: Discussionmentioning
confidence: 99%
“…Surface soil drying is very common during progressive drought and can have a profound impact on root growth, viability and functionality in turfgrass (Huang, 1999). In another study involving bermudagrass, Zhou, Lambrides, Roche, Duff, and Fukai (2013) reported that drought resistant genotypes extracted more soil water than drought sensitive ones, especially at depths from 50-110 cm, resulting in lower canopy temperature, higher photosynthetic rates and relative water contents in leaves. Fuentealba et al (2015) also reported more uniform root distribution throughout the soil profile in common bermudagrass.…”
Section: Discussionmentioning
confidence: 99%
“…A relatively comprehensive study in Australia involving 18 bermudagrass genotypes reported that drought‐resistant genotypes extracted more soil water than drought‐sensitive ones, especially at depths from 50 to 110 cm with lower canopy temperature, higher photosynthetic rate, and relative water content in the leaf. Although root characteristics played a large role in the drought responses of turfgrass, shoot sensitivity to drying soil cannot be ruled out (Zhou et al, 2013, 2014).…”
mentioning
confidence: 99%
“…Consequently, for the first time we show that for turfgrasses there is no adverse effect of selecting for drought resistance in terms of production attributes and quality. In the turfgrass industry, faster regrowth rate after sod removal and a longer period of green cover after drought commences are the criteria for high productivity potential and superior drought resistance, respectively Richardson et al, 2008;Zhou et al, 2013a;Zhou et al, 2013b;Emmons 2008). The positive association between these two criteria lead us to conclude that the mechanisms of plant response are most likely related.…”
Section: Relationship Between Regrowth Quality and Drought Resistancementioning
confidence: 98%
“…The pleiotropic effects of selection for drought resistance are not well understood in perennial C 4 grasses. For turfgrasses, the ability to maintain green cover for longer periods under water deficit is an important criterion of drought resistance Richardson et al, 2008;Zhou et al, 2013a;Zhou et al, 2013b). In terms of production, sod strength and rapid regrowth in non-stress conditions after harvest are important criteria (Emmons 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation